Ivermectin-induced toxicity in HepG2 cells and the protective effect of tetrahydrocurcumin and vitamin C - Miranda, Camila Araújo [UNESP] (2024)
Ivermectin (IVM) is a semi-synthetic antiparasitic derived from abamectin, one of the natural avermectins. The liver promotes metabolism and excretion of IVM, representing a risk of toxicity to this organ. The use of antioxidants to alleviate damage caused by chemicals has been increasingly studied. Thus, the aim of this study was to evaluate the effects of IVM on HepG2 cells to elucidate the mechanisms related to its toxicity and the possible protection provided by tetrahydrocurcumin (THC) and vitamin C. HepG2 cells were treated with IVM (1–25 μM) for 24 and 48 h. IVM was cytotoxic to HepG2 cells, denoted by a dose-dependent decrease in cell proliferation and metabolic activity. In addition, IVM induced damage to the cell membrane at all tested concentrations and for both incubation times. IVM significantly decreased the mitochondrial membrane potential from concentrations of 5 μM (24 h) and 1 μM (48 h). Additionally, IVM showed a time- and dose-dependent decrease in cellular adenosine triphosphate levels. The levels of reduced glutathione were decreased in a time- and dose-dependent manner, while IVM stimulated the production of reactive oxygen and nitrogen species (RONS) at all tested doses, reaching rates above 50% following treatment at 7.5 μM (24 h) or 5 μM (48 h). Treatment with THC (50 μM) and vitamin C (50 μM) protected against IVM-induced cytotoxicity and RONS production. These results suggest that oxidative damage is involved in IVM-induced toxicity in HepG2 cells, and that THC and vitamin C can mitigate the toxic effects caused by the compound.